PENGARUH KEPUTUSAN PENDANAAN, KEPUTUSAN INVESTASI DAN MODAL KERJA TERHADAP NILAI PERUSAHAAN DENGAN PROFITABILITAS SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN MIGAS YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2020-2022 - Rasa, Agus Warmar; Setyawati, Irma (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2024)
The aim of this research is to analyze and obtain empirical evidence of the influence of funding decisions, investment decisions and working capital on company value with profitability as an intervening variable in oil and gas companies listed on the Indonesian Stock Exchange. The research was conducted on 12 companies using the purposive sampling method in selecting samples for the 2020-2022 period. The data analysis method used is the panel data regression method in the Stata 17 application software. The results of this research state that funding decisions (DER) have a positive effect on company value, investment decisions (PER) have a positive effect on company value (PBV), Working capital (NWC) does not have a positive effect on company value (PBV), Profitability (ROA) positive effect on firm value (PBV), Funding decisions (DER) have no positive effect on profitability (ROA), Investment decisions (PER) have a positive effect on profitability (ROA), Working capital (NWC) have no positive effect on profitability (ROA), Decision funding (DER) has no indirect positive effect on firm value (PBV) which is mediated by profitability (ROA), Investment decisions (PER) has an indirect positive effect on firm value (PBV) which is mediated by profitability (ROA), Working capital (NWC) does not have an indirect positive effect on firm value (PBV) which is mediated by profitability (ROA).